Mid-career teacher motivation and implications for leadership practices in secondary schools in Cyprus - Konstantinides-Vladimirou, Katerina (2013)
Teacher motivation can be conveniently interpreted within a framework of motivation theories that are related to the fulfilment of needs (Herzberg, 1968, Maslow, 1954, McClelland, 1961). This thesis argues that mid-career teachers’ motivation is context-specific and relates to the fulfilment of teachers’ needs. Grounded in phenomenology and drawing on semi-structured interviews with twelve mid-career teachers, six headteachers, and six focus groups with thirty-eight students in six lyceums in Cyprus, this qualitative study presents the factors that can motivate secondary teachers with 11 to 20 years of teaching experience to become (more) active in their schools. These factors which constitute the key findings of my study and the contribution of my study to the field of teacher motivation are: the ‘moderators’: recognition, inspection for evaluation, personal life, and experience; and the ‘needs motivators’: satisfaction, collaboration, fairness, and decision making. The ‘moderators’ may determine the extent to which teachers’ ‘needs motivators’ are fulfilled. This study makes a significant contribution to policies designed to enhance leadership practices related to the motivation of mid-career teachers.